Six key approaches to counselling and therapy - Nelson-Jones, Richard (Los Angeles, Calif. ; London : Sage Publications Ltd, 2011)
Following a clearly-defined structure, each chapter describes the origin of the therapeutic approach, a biography of its originator, its theory and practice, discusses case material and further developments, and suggests further reading. Richard Nelson-Jones goes on to review and evaluate all the approaches in his concluding chapter.
Introducing counselling and therapy approaches -- Freud's psychoanalysis -- Jung's analytical therapy -- Person-centred therapy -- Gestalt therapy -- Cognitive therapy -- Solution-focused therapy -- Evaluation eclecticism and integration.
Includes bibliographical references and index.
Keywords: Counseling; Psychotherapy; Counseling; Psychotherapy; Counseling; Psychotherapy; Psychologische Beratung; Psychotherapie; Richtungen; Methode